Crystal structure-based discovery of a novel synthesized PARP1 inhibitor (OL-1) with apoptosis-inducing mechanisms in triple-negative breast cancer - Leilei Fu (Nature Portfolio, 2016)
Abstract Poly (ADP-ribose) polymerase-1 (PARP1) is a highly conserved enzyme focused on the self-repair of cellular DNA damage. Until now, numbers of PARP inhibitors have been reported and used for breast cancer therapy in recent years, especially in TNBC. However, developing a new type PARP inhibitor with distinctive skeleton is alternatively promising strategy for TNBC therapy. In this study, based on co-crystallization studies and pharmacophore-docking-based virtual screening, we discovered a series of dihydrodibenzo[b,e]-oxepin compounds as PARP1 inhibitors. Lead optimization result in the identification of compound OL-1 (2-(11-(3-(dimethylamino)propylidene)-6,11- dihydrodibenzo[b,e]oxepin )-2-yl)acetohydrazide), which has a novel chemical scaffold and unique binding interaction with PARP1 protein. OL-1 demonstrated excellent potency (inhibiting PARP1 enzyme activity with IC50 = 0.079 μM), as well as inhibiting PARP-modulated PARylation and cell proliferation in MDA-MB-436 cells (BRAC1 mutation). In addition, OL-1 also inhibited cell migration that closely related to cancer metastasis and displayed remarkable anti-tumor efficacy in MDA-MB-436 xenograft model without apparent toxicities. These findings highlight a new small-molecule PAPR1 inhibitor (OL-1) that has the potential to impact future TNBC therapy.